A systematic review of the transtheoretical model of behaviour change and alcohol use - Felicíssimo, Flaviane Bevilaqua (2014)
Issues: The study on alcohol has been increasing worldwide due to its social and economic impact, and the illnesses related to alcohol use rank among the most common substance abuse disorders. It seems necessary to further investigate the most effective and suitable treatment methods for different populations. Approach: This paper evaluated the scientific literature on the Transtheoretical Model of Behavior Change related to alcohol consumption. Scopus, Pubmed, PsycInfo, PepsiCo and Lilacs databases were consulted, using the descriptors transtheoretical model, transtheoretical approach, stages of change, processes of change and cycle of change crossed with the descriptor alcoholism, in a ten-year timeframe (2001 to 2011). Key Findings: A majority of researchwith longitudinal and quantitative methods was found in addition to a prevalence of Readiness to Change Questionnaire and University of Rhode Island Change Assessment usage as measuring instruments for Transtheoretical Model. The results indicated that other variables may influence the behavior of the individual in relation to his stage ofchange and identified alcohol-related problems in patients seeking treatment for other health conditions. This finding stresses the need for screening practices for injury prevention related to alcohol use. Implications: The Transtheoretical Model is important in the process of behaviour change, since it allows the identification of the stages and the better adapted interventions based on the patient’s stage that avoids making efforts in the opposite direction to what is demanded by the patient. Conclusion: It is worth emphasizing the need for more studies in this area especially in relation to the practice of health professionals.